Entrainment mechanism of turbulent synthetic jet flow. (10th March 2023) - Xu, Congyi; Long, Yanguang; Wang, Jinjun
Abstract: Abstract : Synthetic jets have received extensive attention due to their superior mixing property. However, its mechanisms have not been investigated from the perspective of the turbulent/non-turbulent interface (TNTI). To shed new light on this issue, the entrainment and TNTI properties of a synthetic jet are experimentally investigated and compared with a continuous jet at $Re_j = 3150$ . The fuzzy clustering method is applied to select an appropriate vorticity threshold to detect the TNTI. Statistically, it is revealed that the entrainment coefficients of the two jets significantly differ in the near field, while they become almost identical in the far field. Instead of the vortex ring, the 'breakdown of the vortex ring' enhances the entrainment in the present synthetic jet. Instantaneously, the TNTI more violently fluctuates in the near field of the synthetic jet, which leads to a larger fluctuation in the TNTI radial position, a higher fractal dimension and enhanced local entrainment. Moreover, the transition of the probability density function of the TNTI orientation from the unimodal distribution in the near field to the bimodal distribution in the far field is found in both jets. The multi-scale analysis reveals a new mechanism for the bimodal distribution caused by the TNTI-thickness-scale structures.